2022
DOI: 10.1002/cbf.3742
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence that cervical cancer cells cultured as tumorspheres maintain high CD73 expression and increase their protumor characteristics through TGF‐β production

Abstract: Recently, a link between the biological activity of CD73 and tumorigenicity in solid tumors has been proposed. We previously reported that the generation of adenosine (Ado) by the activity of CD73 in cervical cancer (CC) cells induces transforming growth factor‐beta 1 (TGF‐β1) production to maintain CD73 expression. In the present study, we analyzed the participation of TGF‐β1 in CD73 expression and the development of protumoral characteristics in CaSki CC cells cultured as tumorspheres (CaSki‐T) and in monola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 62 publications
(153 reference statements)
0
6
0
Order By: Relevance
“…The evaluation of immune molecules' expression on tumor cells could provide the knowledge to comprehend better tumor immune evasion mechanisms. For this purpose, some studies have been focused on using tumorspheres, a 3D model system with outstanding applications for in vitro studies [34,35]. Recently, Bertolini et al reports that spheroid from cell lines are enriched in metastasis initiating cells with immunosuppressive potential [36].…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of immune molecules' expression on tumor cells could provide the knowledge to comprehend better tumor immune evasion mechanisms. For this purpose, some studies have been focused on using tumorspheres, a 3D model system with outstanding applications for in vitro studies [34,35]. Recently, Bertolini et al reports that spheroid from cell lines are enriched in metastasis initiating cells with immunosuppressive potential [36].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that HR‐HPV‐positive CC cells express high CD73 levels in the cell membrane and have a high capacity to generate ADO 40 . Furthermore, we reported that this pathway is important for increasing the protumorigenic characteristics of CC cells, including increased MRP1 expression 41 . Therefore, in this study, we examined the effect of CD73 and the interaction of ADO with ARs on MRP1 expression in CC cells.…”
Section: Introductionmentioning
confidence: 95%
“…40 Furthermore, we reported that this pathway is important for increasing the protumorigenic characteristics of CC cells, including increased MRP1 expression. 41 Therefore, in this study, we examined the effect of CD73 and the interaction of ADO with ARs on MRP1 expression in CC cells. We found that ADO induced an increase in MRP1 expression in CC cells by interacting with A2AR.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, adenosine signaling has emerged as a target in cancer immunotherapy due to its key role in the metabolic pathway that regulates tumor immunity [ 34 ]. In previous studies, we reported that Ado induces the production of TGF-β1 by CeCa cells by interacting with ARs, specifically A 2A R and A 2B R [ 35 ], and that this cytokine strongly contributes to enhancing protumoral characteristics related to tumor progression, such as migration and invasion, immune evasion, immunosuppression, and chemoresistance [ 36 ]. Considering these findings, in this study, we analyzed the role of Ado in the induction of PD-L1 expression in CeCa cells as well as the ability of these cells to inhibit the activation and cytotoxic activity of CD8+ T lymphocytes.…”
Section: Introductionmentioning
confidence: 99%